Macroeconomic regime switches and speculative attacks - Bartosz Maćkowiak (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
This paper explains a currency crisis as an outcome of a switch in how monetary policy and fiscal policy are coordinated. The paper develops a model of an open economy in which monetary policy starts active, fiscal policy starts passive and, in a particular state of nature, monetary policy switches to passive and fiscal policy switches to active. The probability of the regime switch is endogenous and changes over time together with the state of the economy. The regime switch is preceded by a sharp increase in interest rates and causes a jump in the exchange rate. The model predicts that currency composition of public debt affects dynamics of macroeconomic variables. Furthermore, the model is consistent with evidence from recent currency crises, in particular small seigniorage revenues.
Keywords: E52; E61; F33; 330; Coordination of monetary policy and fiscal policy; policy regime switch; currency crisis; speculative attack; fiscal theory of the price level; Geldpolitik; Finanzpolitik; Devisenspekulation; Währungskrise; Theorie